Influence of Ultrasonic Bath on Mold-Assisted Electrodeposition of Gold Microelectrode Arrays - Neeraj Yadav; Flavio Giacomozzi; Alessandro Cian; Damiano Giubertoni; Leandro Lorenzelli (Proceedings)
This study investigates the potential of ultrasonic baths to enhance mold-assisted electrodeposition for fabricating three-dimensional (3D) microelectrode arrays (MEAs) with improved quality and reliability. Focusing on gold microstructures, commonly employed in 3D MEAs due to their biocompatibility and electrical conductivity, we explore how ultrasonic vibrations impact the electrodeposition process. Through the formation of microscopic bubbles and reactive sites, ultrasonic baths accelerate deposition, offering potential benefits such as increased deposition rates, uniformity, and cost-effectiveness. Our experimental findings demonstrate significant improvements in deposition rate and uniformity, highlighting the potential of ultrasonic baths to advance the fabrication of 3D MEAs for various biomedical applications.